x = (-b +/- sqrt(b^2 - 4ac))/2a
where a= 1, b= -6 , c=8
x1 = (6 + sqrt(36 - 32))/2 = 4
x2 = (6 - sqrt4)/2 = 2
2006-11-01 04:33:26
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
y = 0 and x = 2
2006-11-01 13:51:04
·
answer #2
·
answered by Alireza G 1
·
0⤊
1⤋
y = x^2 - 6x + 8 = 0
y = (x-4)(x-2) = 0
the numbers in the brackets have toadd to -6 and multiply to 8
if x-4 = 0 and x-2 = 0 then x = 4 and x = 2
2006-11-01 12:30:15
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
y = x2 - 6x + 8 = 0
can factor to get
(x-4)(x-2)=0
x=4
x=2
using the quadratic formula
x=(6+/-sqrt(36-32))/2=3+/-sqrt(4)/2
x=3+/-1
x=3+1=4
x=3-1=2
2006-11-01 13:03:37
·
answer #4
·
answered by yupchagee 7
·
1⤊
0⤋
x^2 -6x+8 breaks down into (x-2)(x-4)=0, so x-2=0 and x-4=0
x=2,4
2006-11-01 12:27:43
·
answer #5
·
answered by romanwahoo 2
·
1⤊
0⤋
Well the quadratic equation is (-b+-sqrt(b^2-4ac))/2a where a = 1, b = -6 and c = 8.
Good luck. :)
2006-11-01 12:28:31
·
answer #6
·
answered by SmileyGirl 4
·
1⤊
0⤋
y=x^2-6x+8
x^2-6x+8=0
(x-2)(x-4)=0
x=2 and 4
Check:
(2)^2-6(2)+8=0
4-12+8=0
-8+8=0
0=0
(4)^2-6(4)+8=0
16-24+8=0
-8+8=0
0=0
2006-11-01 12:43:12
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
y=x2-6x+8=0
q.e=-b+-under root b2-4ac/2a
=6+-under root36-32/2
=6+-2/2
if it is +2 then answer is 4
if it is -2 then answer is 2
2006-11-01 12:47:00
·
answer #8
·
answered by prasan jain 1
·
1⤊
0⤋
ax^2+bx+c=0
x=[-b+-sqrt(b^2-4ac)]/2a
y=x^2-6x+8=0
a=1
b=-6
c=8
x=[6+-sqrt(36-32)]/2
=[6+-2]/2
=3+-1
=4 or 2
verify
x=4
16-24+8=0 ok
x=2
4-12+8=0 ok
2006-11-01 12:35:47
·
answer #9
·
answered by openpsychy 6
·
1⤊
0⤋
here a=1,b=6,c=8
answer is (6+sqrt(6*6-4*1*8))/(2*1) and (6-sqrt(6*6-4*1*8))/(2*1)
which comes to 4 and 2
2006-11-01 12:31:25
·
answer #10
·
answered by Manish 2
·
1⤊
0⤋